(untitled) (Journal of Informatics Education and Research, 2024)
Customer Relationship Management (CRM) in India’s online retailing industry is greatly improved by artificial intelligence (AI). Artificial intelligence (AI)-powered CRM systems examine enormous volumes of client data to anticipate consumer behaviour, personalise shopping experiences, and make customised product recommendations. For online retailers who are up against fierce competition, this personalisation increases customer happiness and loyalty. AI-driven chatbots and virtual assistants provide immediate customer service by answering questions and addressing problems around-the-clock. In addition to increasing customer service effectiveness, this frees up human resources for more difficult jobs. Additionally, AI systems find trends in customer evaluations and feedback, which aids merchants in resolving issues and improving their products. AI also helps inventory management by forecasting demand patterns, guaranteeing that popular products are always available, and minimising overstock of less well-liked ones. Cost reductions and improved resource allocation result from this. Online merchants in India may simplify processes, build better customer relationships, and keep a competitive edge in a market that is changing quickly by using AI into CRM systems. A sample of 257 was collected from respondents working in retail sector. The factors that identify the Role of Artificial Intelligence (AI) in Effective Implementation of CRM in online Retailing Sector are Predictive Analytics, Automated Customer Service, Enhanced Customer Engagement, and Improved Data Management.